2017
DOI: 10.1002/anie.201702399
|View full text |Cite
|
Sign up to set email alerts
|

From Discrete Molecular Cages to a Network of Cages Exhibiting Enhanced CO2 Adsorption Capacity

Abstract: We have adopted the concept of "cage to frameworks" to successfully produce a Na-N connected coordination networked cage Na-NC1 by using a [3+6] porous imine-linked organic cage NC1 (Nanjing Cage 1) as the precursor. It is found that Na-NC1 exhibits hierarchical porosity (inherent permanent voids and interconnected channel) and gas sorption measurements reveal a significantly enhanced CO uptake (1093 cm g at 23 bar and 273 K) than that of NC1 (162 cm g under the same conditions). In addition, Na-NC1 exhibits v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 46 publications
1
44
0
3
Order By: Relevance
“…They concluded that the CO 2 –sorbent affinity can improve by increasing the imine concentration in the polymer. Most of the molecular crystal sorbents shows the reduction in CO 2 adsorption capacity with increase in adsorption temperature . These results demonstrated that the N‐decorated polymeric sorbent have a great potential as a CO 2 adsorbent.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…They concluded that the CO 2 –sorbent affinity can improve by increasing the imine concentration in the polymer. Most of the molecular crystal sorbents shows the reduction in CO 2 adsorption capacity with increase in adsorption temperature . These results demonstrated that the N‐decorated polymeric sorbent have a great potential as a CO 2 adsorbent.…”
Section: Introductionmentioning
confidence: 74%
“…In last few decades, wide varieties of porous materials like Zeolites, porous carbons, ordered mesoporous silica's (OMS's), metal‐organic frameworks (MOFs), porous organic materials and metal‐organic polyhedral have been developed. Among these porous materials, crystals of covalent organic cage (COC) molecules with porosity is also attracting attention in CO 2 adsorption, including energy storage, chiral separation and sensing for its inherent porosity, high specific surface area, low densities, solubility in various solvents and ease of functional group transformation. In addition to the internal porosity, certain functional groups C≡C, C=N, C–N and N–H which are CO 2 ‐philic in nature have play major role during CO 2 adsorption …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solche Hybridsysteme kçnnten die Vorteile molekularer und lçslicher Käfigeinheiten mit der Robustheit und Haltbarkeit von polymeren Systemen verbinden. [195] Diese ersten Studien sollten nun weitere Entwicklungen inspirieren, die zu noch besseren Strategien fürdie Vernetzung von exohedral funktionalisierten Käfigen führen und einen Zugang zu neuartigen 3D-COFs auf der Basis von Käfigvorstufen erçffnen. In den letzten Jahren gab es bereits einige Pionierarbeiten wie die Implementierung von kovalenten Käfigen in MOFs [191] und nanoporçse Polymere [192] oder die Bildung von Hybridmaterialien durch das synergistische Wechselspiel von sowohl metallosupramolekularen als auch dynamisch-kovalenten Bindungsknüpfungen.…”
Section: Käfig-zu-netzwerk-strategienunclassified
“…Mononuclear Zn II Schiff-base complexes are known to form dimeric structuresh aving at ypical Zn 2 O 2 central unit, mediated by strong intermolecularZ n ÀOc oordinative interactions (through m 2 -phenoxob ridging). [33][34][35][36][37][38] Oneo ft he main synthetic challenges is to obtain selectively one type of macrocycle of ag iven size in good yield. [7][8][9][10][19][20][21] In particular,t he aggregation behavior of multinuclear Zn II salphen complexes is strongly enhanced owing to their unusual oligomeric (ZnÀO) n coordination motifs, ap eculiar property that has been exploited for the construction of self-assembled nanostructures of very high stability.…”
Section: Introductionmentioning
confidence: 99%